2011
DOI: 10.1002/app.35036
|View full text |Cite
|
Sign up to set email alerts
|

Triply‐responsive (thermo/light/pH) copolymeric hydrogel of N‐isopropylacrylamide with an azobenzene‐containing monomer

Abstract: A series of triply-responsive copolymer hydrogel was firstly synthesized via free radical polymerization of N-isopropylacrylamide, 4-[(4-(acryloyloxy)ethoxy) phenylazo]benzoic acid (AEPAZA), a water-soluble azobenzene-containing comonomer, and crosslinker. The properties of the hydrogel were subsequently investigated by UV-Vis absorption spectrometry, differential scanning calorimetry, and gravimetry. UV-Vis spectra showed that the copolymer hydrogel had a reasonable tran-cis photoisomerization rate upon UV ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…In order to improve and increase their applicability, several smart polymers have been developed to combine two or more mechanisms of responsiveness in only one material [41,42] . A quite common approach involves preparing polymers sensible to both temperature and pH stimuli [43][44][45][46][47][48][49][50][51][52][53][54][55] , since they are typical variables parameters in biological and chemical systems, and they can also be easily controlled in vitro and in vivo conditions [56][57][58][59] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve and increase their applicability, several smart polymers have been developed to combine two or more mechanisms of responsiveness in only one material [41,42] . A quite common approach involves preparing polymers sensible to both temperature and pH stimuli [43][44][45][46][47][48][49][50][51][52][53][54][55] , since they are typical variables parameters in biological and chemical systems, and they can also be easily controlled in vitro and in vivo conditions [56][57][58][59] .…”
Section: Introductionmentioning
confidence: 99%
“…Photo‐, thermo‐ and pH‐responsive PNIPAM‐allylamine copolymer microgels coupled with spiropyran photochromes were synthesized by Garcia et al, the swelling capability of which exhibited multi‐stimuli responsiveness as revealed by dynamic light scattering 162. Triply responsive (light/pH/T) hydrogels could be synthesized via free‐radical polymerization of N ‐isopropylacrylamide and 4‐[(4‐(acryloyloxy)ethoxy)phenylazo]benzoic acid, an azobenzene‐containing monomer, and crosslinker 163. Recently, uniform multi‐stimuli‐responsive hydrogel photonic crystal microparticles (HPCMs) with inverse‐opal structure were generated through a combination of microfluidic and templating techniques by Zhu et al Temperature‐ and pH‐responsive HPCMs were firstly prepared by copolymerizing N ‐isopropylacrylamide and methacrylic acid, which not only showed tunable color variation almost covering the entire wavelength range of visible light by simply tailoring temperature or pH value of the solution, but also displayed rapid response (less than 1 min) due to the small volume and well‐ordered porous structure.…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%
“…On the one hand, azobenzenes are strongly hydrophobic moieties that can reduce water solubility markedly when incorporated even in small amounts 16, 27. On the other hand, the photoinduced changes in the LCST between the polymers bearing azobenzenes in the trans ‐ and in the cis ‐state, respectively, vary between marked to very weak, without following an obvious rational 8, 14–30. Whereas, for instance, Ishii et al24 did not observe any changes of the cloud points (CPs) upon irradiation of azobenzene end‐capped PNIPAM, Shimoboji et al28 as well as Akiyama and Tamaoki18 reported a temperature difference between the cloud points of the trans ‐ and the cis ‐forms ($ \Delta T_{\rm CP}^{cis-trans} $ ) of up to 10 °C.…”
Section: Introductionmentioning
confidence: 99%